Performatyka – teoria katastrof? - Wojnowski, Konrad (Wydawnictwo Naukowe UAM, 2014)
The author of Performatyka – teoria katastrof? [“Performance studies – the theory of catastrophes?”], which is a cross-sectional investigation into performance studies, tracks the trains of thought about catastrophes in different theories of performativity, ranging from J. L. Austin’s to Jon McKenzie’s ideas. Of particular interest is how particular theoreticians integrate the term ‘catastrophe’ into their conceptual frameworks and how they evaluate it. By criticizing the approach taken by Judith Butler, who postulates “melancholic performance studies”, which brings to mind Adorno’s idea that is explicated in Minima Moralia (traurige Wissenschaft), the author tries to show how we can productively use Austin’s theses that are presented in the first chapters of his famous How to Do Things with Words. In the author’s opinion, Austin allows us to approach communicational catastrophes from a different perspective, which is often forgotten, i.e. of the functioning of contextual systems. It is shown that the tension between felicity and infelicity may be at the core of the popularity of performativity which is understood as a tool for researching contemporary cultural phenomena.
Performance studies – the theory of catastrophes?